A phase II randomized trial of individualized neoantigen peptide vaccine combined with unusual radiotherapy (iNATURE) in advanced solid tumors-GCOG0028 - Zhang, Yan; Hu, Ye-Fan; Ma, Lingyu; Wu, Yifei; Chao, Dandan; Chen, Xian; Xu, Zhiyuan; Su, Xiaoping; Dai, Wei; Huang, Jiandong; Fu, Pingfu; Kong, Feng-Ming (Spring) (Frontiers in Immunology, 2025)
BackgroundNeoantigen-based vaccines show promising therapeutic potential in solid tumors such as melanoma, GBM, NSCLC, and CRC. However, clinical responses remain suboptimal in stage IV patients, due to ineffective T-cell function and high tumor burdens. To overcome these limitations, our study investigates a combination strategy using neoantigen peptide vaccines and precision critical lesion radiotherapy (CLERT), which delivers immunomodulatory doses to key tumor regions synergistically enhance immune activation and inhibit progression in multifocal stage IV patients.Materials/MethodsThis is an open-label, multicenter phase II randomized study. The main objective is to evaluate the anti-tumor efficacy of personalized tumor neoantigen peptide vaccines and assess how different radiation doses synergize with vaccination in treating patients with advanced malignant tumors who have progressed after systemic therapy. Patients are stratified by cancer type and randomized 1:1 to receive either placebo with conventional treatment (including high and low dose radiotherapy) or a personalized neoantigen peptide vaccine alongside conventional treatment (including high and low dose radiotherapy). A one-way crossover design is implemented, permitting patients in the placebo arm to transition to the experimental arm upon progression. Clinical outcomes including progression-free survival and objective response rate are assessed both before and after crossover. Key inclusion criteria are as follows: 1) Patients with advanced or recurrent cancers detected by pathology and imaging, who failed first-line treatments; 2) Patients with projected survival ≥3 months and an ECOG score of 0-2; and 3) Patients with at least one predicted high-quality tumor neoantigen.ConclusionThis trial introduces an innovative combination strategy of precision radiotherapy and neoantigen vaccine. A notable feature of this study is the incorporation of a randomized control and intra-group crossover design, which is rarely utilized in neoantigen trials. The study is designed to provide critical insight into radiation-immune synergy and the clinical benefit of personalized immunization. Additionally, a basket-trial framework is employed, leveraging shared neoantigens across cancer types to improve efficiency and generalizability. This approach may reduce preparation time and cost, facilitating broader implementation of neoantigen-based immunotherapies. Altogether, this trial design represents a significant step toward translational application of tumor neoantigen vaccines and provides a platform for future combinational immunotherapy strategies.Trial registrationhttps://clinicaltrials.gov/study/NCT06314087, identifier: NCT06314087; www.chictr.org.cn, identifier: ChiCTR2300078055. Global Collaborative Oncology Group (GCOG) identifier: GCOG0028.